2017
DOI: 10.1103/physrevd.96.062004
|View full text |Cite
|
Sign up to set email alerts
|

Capacitive sensing of test mass motion with nanometer precision over millimeter-wide sensing gaps for space-borne gravitational reference sensors

Abstract: Capacitive sensing of test mass motion with nanometer precision over millimeter-wide sensing gaps for space-borne gravitational reference sensors. Physical Review D, 96(6), 062004.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/148989/ We report on the performance of the capacitive gap-sensing system of the Gravitational Reference Sensor (GRS) onboard the LISA Pathfinder (LPF) spacec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 23 publications
0
45
0
2
Order By: Relevance
“…green) or by enhancing the reddening of the noise of z 1 and z 2 sensors. To remove this ambiguity, the reddening (1/f behaviour) has been measured independently by [13]. Figure 5 shows the behaviour of the z 2 sensing output.…”
Section: The Drag-free and Attitude Control System (Dfacs) -mentioning
confidence: 99%
See 2 more Smart Citations
“…green) or by enhancing the reddening of the noise of z 1 and z 2 sensors. To remove this ambiguity, the reddening (1/f behaviour) has been measured independently by [13]. Figure 5 shows the behaviour of the z 2 sensing output.…”
Section: The Drag-free and Attitude Control System (Dfacs) -mentioning
confidence: 99%
“…We used therefore the results of independent and dedicated investigations that were performed during the mission. For the capacitive sensing noises, we refer to [13] which showed that these noises had a 1 / f (in amplitude) dependence below 1mHz whereas, for the capacitive actuation noises, [14] showed a 1 /f dependence (in amplitude) below 1mHz. We have performed an analysis of all the observables (x, y, z, θ, η and φ) associated to TM 1 for a number of noise only runs.…”
Section: The Drag-free and Attitude Control System (Dfacs) -mentioning
confidence: 99%
See 1 more Smart Citation
“…A pair of carrier waves, which are +V p and −V p with equal amplitude and opposite phase, are injected into the two fixed plates. Therefore, the differential capacitance ∆C information is converted to voltage information and picked up by the charge amplified by V charge [17].…”
Section: Principle Of Capacitive Transducersmentioning
confidence: 99%
“…The other TM (labeled TM2) is actuated, such that it follows the spacecraft and TM1. The main LPF observable, Dg, is the total residual acceleration of the two TMs in free fall condition, along the main measurement axis x, and it is calculated by 6,7 Dg(t) =ẍ 12…”
mentioning
confidence: 99%